Виявлення залежності між сеансовими ключами ецп ecnr стандарту ISO/IEC 15946-4 - Шевчук, О. А. (ХНУРЭ, 2009)
In modern schemes of digital signature signing algorithm divided in two steps: generation of pre-signature, and signing message with pre-signature. Main component of pre-signature is session key. Session key must be received absolutely randomly. Discovered situation when certain connection between session keys may be detected